Face recognition using Eigenface/PCA / Muhammad Fadzli Ahmad Jalalulmahalli - Muhammad Fadzli, Ahmad Jalalulmahalli (2005)
Biometric is an area which deals with that of recognition processes, whether it be that of the iris scan, fingerprints, retina scan, voice recognition and face recognition. As for this thesis, the title is face recognition, which deal with the recognition of faces using computational methods. The algorithm that was adopted for this particular projects is the eigenfance algorithm, which reprocesses a set of face images into eigenvectors, or of ghostly faces, that shall be used as the base for the recognition process. After the pre-processing has been done, a single face image file is fed to the system and pre-processed into an eigenfance, and that eigenface shall be mapped to be eigenfaces of the set of face images, and recognition is done, by calculating the similarities between them. The result of the recognition process is that, if the faces is classified as a known face, then it will be displayed, and if it is not a known face, then it will not be displayed.